VESICOCUTANEOUS FISTULA AND BLADDER INJURY IN POST HYSTERECTOMY PATIENT: A CASE REPORT - Mahendra Yudha Pratama; William Tendi; Octoveryal Aslim; Andhika Hernawan Novianda (Jurnal Urologi Indonesia)
Objective: This article presents a case of vesicocutaneous fistula and bladder injury with intraabdominal adhesion in post-caesarian section and hysterectomy patients. Case(s) Presentation: A 29-year-old woman suffering from vesicocutaneous fistula and bladder injury 10 days after having a hysterectomy due to atonic uterus in post-caesarian delivery. Discussion: Cystography and cystoscopy confirmed the bladder perforation at the posterior and dome. Exploratory laparotomy was then performed and found that a bowel adhesion had occurred following the inflammatory process after the previous procedure. A bladder reconstruction was then performed, and the patient was then catheterized for almost two weeks. Conclusion: A routine follow up then revealed the patient had no more symptom and the surgical wound was closed without any further complication.